Efektivitas Restoratif Justice Terhadap Pungutan Liar Mobil Pasir Di Wilayah Hukum Pancur Batu - Rajagukguk, Jonatan; Mubarak, Ridho (Universitas Medan Area, 2025)
This research discusses the effectiveness of the application of the Restorative Justice approach in handling cases of illegal levies against sand transportaion trucks within the jurisdiction of the Pancur Batu Police Sector. Illegal levies are a form of criminal offense that harms the community and undermines the integrity of law enforcement officers. Restoratife Justice offers and alternative for resolving criminal cases by focusing on the recovery of loses, agreements, active participation of the victim, perpetrator and the community. This study uses a Normative Juridical Method combined with Descriptive Analysis, covering the effectivenesess of the impletation of Restorative Justice in resolving illegal levy cases involving sand trucks in the Pancur Batu Police Sector. The Normative Juridical approach is a legal research method conducted by examining legal literature or secondary legal materials. The data analysis method used is Qualitative Analysis, conducted by systematically describing the data collected with qualitative measures. The result show that Restorative crimes. Strengthening regulations, enhancing the capacity of lawenforcement officers and conducting community outreach are key to the succesfull implementaion of Restorative Justice in local context.